2011
DOI: 10.1038/nature10657
|View full text |Cite
|
Sign up to set email alerts
|

An equilibrium-dependent retroviral mRNA switch regulates translational recoding

Abstract: Most retroviruses require translational recoding of a viral messenger RNA stop codon to maintain a precise ratio of structural (Gag) and enzymatic (Pol) proteins during virus assembly1,2. Pol is expressed exclusively as a Gag–Pol fusion either by ribosomal frameshifting or by read-through of the gag stop codon3. Both of these mechanisms occur infrequently and only affect 5–10% of translating ribosomes, allowing the virus to maintain the critical Gag to Gag–Pol ratio4–8. Although it is understood that the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(159 citation statements)
references
References 28 publications
(36 reference statements)
6
150
0
Order By: Relevance
“…An RNA pseudoknot structure (MoMLV-PK) is responsible for allowing translational readthrough of the MoMLV gag stop codon via termination suppression (reviewed in reference 4). Nuclear magnetic resonance-based structural studies demonstrate that, at physiological pH, the pseudoknot adopts a conformation permissive for stop codon readthrough in approximately 6% of MoMLV RNAs, whereas a nonpermissive conformation is observed in the remaining 94% (5). These ratios correlate well with the 20:1 Gag/Gag-Pol ratio reported for MLV (6).…”
supporting
confidence: 64%
“…An RNA pseudoknot structure (MoMLV-PK) is responsible for allowing translational readthrough of the MoMLV gag stop codon via termination suppression (reviewed in reference 4). Nuclear magnetic resonance-based structural studies demonstrate that, at physiological pH, the pseudoknot adopts a conformation permissive for stop codon readthrough in approximately 6% of MoMLV RNAs, whereas a nonpermissive conformation is observed in the remaining 94% (5). These ratios correlate well with the 20:1 Gag/Gag-Pol ratio reported for MLV (6).…”
supporting
confidence: 64%
“…It is possible that selectivity in read-through for conventional stop codons differs from that of PTCs. Moreover, numerous factors may influence translation fidelity, including nucleotides up to six bases away from the stop codon (33,34), translation factors (35), and local mRNA tertiary structure (36).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, for several viral pseudoknots, as long as their conformation and overall stability is maintained, the exact nucleotide sequence may not be important (Giedroc and Cornish 2009). On the other hand, it was recently demonstrated that the murine leukemia virus (MLV) pseudoknot regulates translational recoding by a protonation-dependent conformational switch that involves interactions of the stem with the loop (Houck-Loomis et al 2011). Although the Ty1 G6A mutant did not show substantial reactivity changes in the pseudoknot region, our clustering analysis demonstrated that this mutant is distinct from the WT in global structure.…”
Section: A Model For the 3-d Structure Of The Pseudoknotmentioning
confidence: 99%